Determination of the Nutritional Habits of the Primary Teacher Candidates for the Game and Physical Activities Teaching Course - Arzu Pekğöz Çeviker; Mustafa Önder Şekeroğlu (Journal of Educational Issues, 2024)
Today, countries implement policies and programs for childhood obesity. However, the effect of classroom teachers in preventing obesity is in a position to be a role model for students. Therefore, the awareness of the pre-service classroom teachers about nutrition and their nutritional behaviors have an important place on the students. On the other hand, a regular and correct nutrition behavior that the teacher candidates who are trained in the primary school teaching program will receive can gain this behavior to the students they will teach. In addition, there is a balanced and regular eating habit in the physical activity and nutrition section of the Physical Education and Play Lesson Curriculum in primary schools. In this study, it was aimed to examine the dietary habits of primary school teacher candidates. For this purpose, the questionnaire revealing the eating habits was applied to the primary school teacher candidates. In the analysis of the data, percentage and frequency tests were performed with the SPSS program. In the research results; it was discovered that most of the primary school teacher candidates did not receive nutrition education, did not have alcohol and smoking habits, and did not engage in any sports activities. It has been stated that almost all of the primary school teacher candidates have the habit of breakfast, but they skip meals, and the most skipped meal is lunch. They stated that the reason for skipping meals was that they did not have the opportunity. It was seen that the majority of the participants consume less than two liters of water per day and less than five cups of tea/coffee per day. As a result of the study, it was determined that the primary school teacher candidates’ nutritional habits and knowledge levels were deficient.